Additives for Cycle Life Improvement of High‐Voltage LNMO‐Based Li‐Ion Cells. Issue 20 (17th October 2019) - Hofmann, Andreas; Höweling, Andres; Bohn, Nicole; Müller, Marcus; Binder, Joachim R.; Hanemann, Thomas
Abstract: In this empirical study, five electrolyte additives, namely, lithium bis(oxalato) borate, lithium difluoro(oxalato) borate, 1‐vinyl‐1, 2, 4‐triazole, 1‐vinyl imidazole and dimethyl‐2, 5‐dioxahexane dioate are described and compared regarding their effect in LNMO//graphite cells. The additives were selected from a preliminary study of 59 potential additives. The basis electrolyte mixture is DMC/EC+1 M LiPF6 (LP30) for all cells. All additives are able to enhance the cycle life at room temperature and at elevated temperatures (50 °C) significantly compared to the non‐additive electrolyte blend (basis electrolyte). The cell enhancement is discussed based on the solid‐electrolyte interface (SEI) and metal‐ion content on anode side. The aim of the study is to suggest promising already known as well as new additives that are able to overcome the issue of rapid capacity fading of LNMO‐based cells when the cells are cycled up to 4.8–5.0 V vs. Li/Li +, especially at higher temperatures. Abstract : A fine selection : In this study selected additives are described and compared regarding their effect in LNMO//graphite cells. All additives are able to enhance the cycle life at room temperature and at elevated temperatures (50 °C) significantly compared to the non‐additive electrolyte blend (DMC/EC+1 M LiPF6 ). The aim of the study is to suggest promising additives that are able to overcome the issue of rapid capacity fading of LNMO based cells when the cells are cycled up to 5.0 V vs. Li/Li + .